Terapi Sel Punca dan Tata Laksana Covid-19 - Dito Anurogo; Zahradiva Putu Fitria Hermawan; Nur Rahmah Awaliah; Taruna Ikrar (MEDICINUS, 2023)
Covid-19 was first identified in Wuhan, China, and known as a disease that can damage the lungs, as well as other organs and system organs such as the heart and the immune system. To date, there is no specific treatment for this disease, however, scientists in China have conducted many clinical studies of cell-based therapies for patients with Covid-19 and other respiratory diseases, especially mesenchymal stem (stromal) cells (MSC), by utilizing MSC-derived conditioned media (CM) or extracellular vesicles and several other cell types. Recent preclinical data from respiratory viral infection models and clinical studies related to the use of MSCs by altering the expression of proinflammatory cytokines, and facilitate the repair of damaged tissue in Covid-19 patients. This research method uses descriptive case study method. The purpose of this study was to determine the effectiveness of therapy using stem cells or mesenchymal stem cells (MSCs) in the management of Covid-19. The results suggest that administration of allogeneic MSCs could accelerate the process of tissue repair in the lungs, thus reducing the need for further mesenchymal cell activation. Positive responses in subjects receiving UC-MSC treatment indicated a decrease in inflammatory cytokines, rather than a change in viral load. The high cost of cell therapy makes researchers only able to conduct limited clinical studies on cell therapy for Covid-19 patients.